Molecular communication between host plant and the fungal tomato pathogen Cladosporium fulvum - De Wit, P.J.G.M.; Joosten, M.H.A.J.; Honee, G.; Wubben, J.P.; Van Den Ackerveken, G.F.J.M.; Van Den Broek, H.W.J.
Host genotype specificity in interactions between biotrophic fungal pathogens and plants in most cases complies with the gene-for-gene model. Success or failure of infection is determined by absence or presence of complementary genes, avirulence and resistance genes, in the pathogen and the host plant, respectively. Resistance, expressed by the induction of a hypersensitive response followed by other defence responses in the host, is envisaged to be based on recognition of the pathogen, mediated through direct interaction between products of avirulence genes of the pathogen (the so-called race-specific elicitors)and receptors in the host plant, the putative products of resistance genes. The interaction between the biothrophic fungus Cladosporiumfulvum and its only host tomato is a model system to study fungus-plant gene-for-gene relationships. Here we report on isolation, characterization and biological function of putative pathogenicity factors ECP1 and ECP2 and the race-specific elicitors AVR4 and AVR9 of C. fulvum and cloning and regulation of their encoding genes. Disruption of ecpl and ecp2 genes has no clear effect on pathogenicity of C. fulvum. Disruption of the avr9 gene, which codes for the race-specific 28 amino acid AVR9 elicitor, in wild type avirulent races, leads to virulence on tomato genotypes carrying the complementary resistance gene Cfl). The avirulence gene avr4 encodes a 105 amino acid race-specific elicitor. A single basepair change in the avirulence gene avr4 leads to virulence on tomato genotypes carrying the Cf4 resistance gene.
Keywords: PATHOGENICITY GENES; AVIRULENCE GENES; RACE-SPECIFIC ELICITORS; RESISTANCE GENES; HYPERSENSITIVE RESPONSE; HOST DEFENSE RESPONSES